KEPENTINGAN INDONESIA MENJALIN KERJASAMA ENERGI MINYAK BUMI DAN GAS DENGAN PERANCIS TAHUN 2011 – 2013 - Bony Haranda; Pazli " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research explains about the Indonesian interests cooperation oil and gas energy with France in 2011 – 2013. France is a country of several major countries are making huge investments in Indonesia. The advance of France technology in exploration of oil and gas energy is a reason for Indonesia for accepted the cooperation about oil and gas energy. The cooperation is expected to further increase the production of oil and gas for Indonesia. The cooperation also have an impact for economic incrase in Indonesia. The data sources that is used on this research are obtained trought bookes, joournals, teraties, documents, websites, online media, and also earlier related research. To analyse the researche question, researcher use nation state as the analysis level with International Trade and also the national interest concept. Prespective that researches use is merkantilism prespective. This research is intended to show that the cooperation of Indonesian and France is impact for the raising of oil and gas energy ratio in Indonesia. The cooperation of Indonesian and France also made an impact for economic growth ratio for Indonesian. The good attitude of Indonesian and France shown to made the relationship of the countries making better every year.Keywords : Energy, National Interest, International Trade, Merkantilism prespective.